1994
DOI: 10.1212/wnl.44.7.1198
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral seventh nerve palsy

Abstract: Among inpatients with facial diplegia, one-half (22 patients) had benign, self-limited causes, including Bell's palsy (10), Guillain-Barré syndrome (5), multiple idiopathic cranial neuropathies (3), brainstem encephalitis (2), Miller Fisher syndrome (1), and association with benign intracranial hypertension (1). Nine patients had tumors: four meningeal, three prepontine, and two intrapontine. Syphilis (2 patients), Hansen's disease (1), cryptococcal meningitis with acquired immunodeficiency syndrome (1), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
102
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 4 publications
1
102
1
2
Order By: Relevance
“…8 A review article by Keane found that 2 of 43 cases of bilateral facial nerve palsy were induced by syphilis infection. 7 A potential differential diagnosis of bilateral facial nerve palsy could be syphilitic meningitis, which was reported by Merritt et al to be the most common etiology involving cranial nerves, especially the facial and auditory nerves. 9 In an analysis of 34 patients, unilateral facial nerve involvement was noted in 16 cases, whereas bilateral palsy was observed in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 A review article by Keane found that 2 of 43 cases of bilateral facial nerve palsy were induced by syphilis infection. 7 A potential differential diagnosis of bilateral facial nerve palsy could be syphilitic meningitis, which was reported by Merritt et al to be the most common etiology involving cranial nerves, especially the facial and auditory nerves. 9 In an analysis of 34 patients, unilateral facial nerve involvement was noted in 16 cases, whereas bilateral palsy was observed in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a 23-year review, Keane et al found that out of 43 patients with FD as the predominant sign, GBS were one of the common underlying causes. Among the cases, two out of the five with GBS progressed clinically; information on the others was not available 2 . Eleven patients (64.7%) were diagnosed with GBS in our study, one of them presented with FD at the onset of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the etiology of FD includes many conditions such as congenital, Bickerstaff ' s brainstem encephalitis, tuberculous meningitis, sarcoidosis traumatic, Lyme disease, diabetes mellitus, metabolic, toxic (thallium), and immunoallergic 2,16,17,18,19,20,21,22,23 . In our study, we did not detect Hansen' s disease, syphilis, Lyme disease, intracranial tumors or cryptococcal meningitis, unlike the studies from Keane et al…”
mentioning
confidence: 99%
“…A comprehensive review of GBS in pregnancy showed that plasmapheresis and IVIG were both effective and safe in the treatment of GBS in pregnancy. IVIG might be a better choice for GBS during pregnancy because it does not involve important alterations in blood volume (9). GBS per se is not an indication for pregnancy termination because there is evidence that it does not shorten disease duration or improve maternal outcomes (19).…”
Section: Discussionmentioning
confidence: 99%